2014
DOI: 10.1080/09168451.2014.882746
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of oleaginous yeast (Rhodosporidium toruloides) mutants tolerant of sugarcane bagasse hydrolysate

Abstract: Rhodosporidium toruloides is a lipid-producing yeast, the growth of which is severely suppressed when hydrolysates of lignocellulosic biomass are used as carbon source. This is probably due to the toxic substances, such as organic acids, furans, and phenolic compounds produced during the preparation of the hydrolysates. In order to solve this problem, R. toruloides cultures were subjected to atmospheric room-temperature plasma mutagenesis, resulting in the isolation of mutants showing tolerance to sugarcane ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Wild isolates of R. toruloides can produce lipids and carotenoids from a wide variety of carbon sources including glucose ( Wiebe et al, 2012 ), xylose ( Wiebe et al, 2012 ), and acetate ( Huang et al, 2016 ), as well as complex biomass hydrolysates ( Fei et al, 2016 ). They are relatively tolerant to many forms of stress including osmotic stress ( Singh et al, 2016 ) and growth-inhibiting compounds in biomass hydrolysates ( Hu et al, 2009 ; Kitahara et al, 2014 ). Rhodosporidium toruloides has been engineered to produce lipid-derived bioproducts such as fatty alcohols ( Fillet et al, 2015 ) and erucic acid ( Fillet et al, 2017 ) from synthetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Wild isolates of R. toruloides can produce lipids and carotenoids from a wide variety of carbon sources including glucose ( Wiebe et al, 2012 ), xylose ( Wiebe et al, 2012 ), and acetate ( Huang et al, 2016 ), as well as complex biomass hydrolysates ( Fei et al, 2016 ). They are relatively tolerant to many forms of stress including osmotic stress ( Singh et al, 2016 ) and growth-inhibiting compounds in biomass hydrolysates ( Hu et al, 2009 ; Kitahara et al, 2014 ). Rhodosporidium toruloides has been engineered to produce lipid-derived bioproducts such as fatty alcohols ( Fillet et al, 2015 ) and erucic acid ( Fillet et al, 2017 ) from synthetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…the mutagenesis with EMS increased the total lipid content of mutant strain from 16.2 ± 2.6% in day 10 to 50.8 ± 6.8% in day 18 representing 1.5 to 2 times higher than that of wild strain (7.6 ± 1.8% in day 10 to 34.0 ± 3.8% in day 18). Kitahara et al [38] reported that all mutant strains of Rhodosporidium toruloides showed higher lipid productivity than the wild type (WT). In this study, the biomass and lipid yield of wild RmTun15 were higher than that for R. mucilaginosa [39].…”
Section: Resultsmentioning
confidence: 99%
“…The plates were incubated at 30 °C for 3-6 days with regular observation for yeast growth. The obtained single yeast colonies were picked-up and sub-cultured on fresh YEPD medium (20 g/L glucose, 20 g/L peptone, 10 g/L YE, 15 g/L agar and seawater (50% v/v)) and incubated at 30 °C for 48 h to obtain pure cultures [23].…”
Section: Yeast Strains Isolationmentioning
confidence: 99%